His Reputation Precedes Him: Examining the Construction and Management of the Pimp in Strip Clubs. Issue 1 (2nd January 2020) - Law, Tuulia
ABSTRACT: Narratives of dancers and managerial individuals working in strip clubs in Ontario, Canada, reveal that even within the sex industry the dominant image of the pimp—as an exploitative, racialized, underclass villain—informs the perception of certain men, characteristics, and relationships. To make sense of this phenomenon, this article applies Baudrillard's concept of simulacrum to examine the circulation of the pimp trope amongst strip club workers. In so doing it argues the pimp stereotype deviantizes dancers' relationships, and black men, as the same time as its narrow focus diverts attention away from various personal and professional challenges dancers may face.